Identification of an enveloped phage, mycoplasma virus L172, that contains a 14-kilobase single-stranded DNA genome. - Dybvig, K (1985)
We have found that mycoplasma virus L172 is an enveloped globular virion containing circular, single-stranded DNA of 14.0 kilobases. L172 has been reported by other workers to have a double-stranded DNA genome of 13 to 17 kilobase pairs and has been classified as a plasmavirus, a group for which mycoplasma virus L2 is the type member. Mycoplasma viruses L172 and L2 differ in genome size and structure, DNA base composition, and protein composition, and they have no detectable DNA homology. As the only reported enveloped virion containing single-stranded DNA, L172 represents a new group of viruses.